Natural Resources Research - Natural Resources Research (Springer Nature, 2026)
This journal publishes quantitative studies of natural (mainly but not limited to mineral) resources exploration, evaluation and exploitation, including environmental and risk-related aspects. Typical articles use geoscientific data or analyses to assess, test, or compare resource-related aspects. NRR covers a wide variety of resources including minerals, coal, hydrocarbon, geothermal, water, and vegetation. Case studies are welcome.
FI 1.36
Q1
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Energía geotérmica; Explotación de recursos naturales; Aspectos ambientales y de riesgo